An epidemic of silicosis among former denim sandblasters - Akgun, M; Araz, O; Akkurt, I; Eroglu, A; Alper, F; Saglam, L; Mirici, A; Gorguner, M; Nemery, B (The European respiratory journal, 2008)
Sandblasting denim using silica has emerged as a new cause of silicosis in Turkey. Following the discovery of several cases of silicosis in (young) workers who used this process, the frequency and main occupational risk factors of silicosis among former denim sandblasters in the region of Erzurum (Turkey) were evaluated. Demographic characteristics and information on working conditions were obtained by questionnaire and interview. In addition, spirometry testing was performed and chest radiographs were evaluated according to International Labour Office (ILO) classification of pneumoconioses in 157 former denim sandblasters. All subjects were male, with a mean (range) age of 23 (15–44) yrs. They had worked for a mean (range) of 36 (1–120) months, starting employment at a 17 (10–38) yrs of age. Most subjects (83%) had respiratory symptoms, especially dyspnoea (52%) but also chest pain (46%). Radiological evidence of silicosis (ILO score 1/0 or higher) was present in 77 (53%) out of 145 subjects with interpretable chest radiographs. These subjects had lower forced expiratory volume in one second and forced vital capacity. The risk of silicosis correlated with seniority ( i.e. working as a foreman), exposure duration and number of places of work. Considering the high prevalence rate of silicosis in such workplaces, further problems are inevitable in the future unless effective measures are taken.